ANALISIS PELAYANAN PENGURUSAN AKTE KELAHIRAN ANAK DI KOTA PEKANBARU - ", Syamsul; Sahuri, Chalid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Analysis of Birth Certificate Child Care Arrangements in Peknabru City.Service is one of the things that really need to get the attention of the government, sothat the user community services were satisfied with the service provided. In relationto the above Department of Population and Civil Registration Pekanbaru City is oneof the agencies authorized to provide services to the community, especially in theareas of service birth certificate.Birth certificate is a certificate issued by the competent authority, which isrelated to the birth in order to acquire or obtain legal certainty against someone. Deedmade based on reports of births conveyed within the time limit no later than 60(sixty) working days for the citizen and 10 (ten) working days from the date of birthfor foreigners baby.This research uses descriptive qualitative research method. Researchers aretrying to reveal the facts in accordance with the reality. This study does not seek orexplain relationships, not to test hypotheses or make predictions. The data will bedescribed by what it is so it can be an understanding.From the research it can be concluded that the Birth Certificate Child CareArrangements in Pekanbaru city has not done well. It can be seen from the results ofthe interviews and the data that has been presented previously that of indicators ofprofessionalism and skills, attitudes and behaviors, and trustworthy reliability,accessibility and flexibility, repair, reputation and credibility of the Birth CertificateChild Care Arrangements in City Pekanbaru not run with the maximum there are stillthings that are not in accordance with the Standard Operating Procedure which has beapplicable.Key words: Care, Birth Certificate, Department of Population and Civil Registration